Facile synthesis of 2D Zn(II) coordination polymer and its crystal structure, selective removal of methylene blue and molecular simulations - Sezer, Gunes Gunay; Yesilel, Okan Zafer; Sahin, Onur; Arslanoglu, Hasan; Erucar, Ilknur (Elsevier, 2017)
A new coordination polymer {[Zn(mu(3)-ppda)(H2O)(mu-bpa)Zn(mu-ppda)(mu-bpa)]center dot 4H(2)O)(n) (1) (ppda = 1,4-phenylenediacetate, bpa = 1,2-bis(4-pyridyl)ethane) has been synthesized by microwave-assisted reaction and characterized by elemental analysis, IR spectroscopy, single-crystal and powder X-ray diffractions. The asymmetric unit of 1 consists of two Zn(II) ions, two bpa ligands, two ppda ligands, one coordinated and four non-coordinated water molecules. In 1, ppda(2-) anions are linked the adjacent Zn(II) centers to generate 1D double-stranded chains. These chains are connected into 2D sheets by the bridging bpa ligands. Atomically detailed modeling was performed to compute single and binary component adsorption isotherms of H-2, CO2, CH4 and N-2 in complex 1. Results showed that 1 exhibits a high adsorption selectivity towards CO2 due to its high affinity for CO2. Results of this study will be helpful to guide the microwave-assisted reaction of coordination polymers to design promising adsorbents for gas storage and gas separation applications. The luminescent property of 1 and the selective removal of dyes in I have been also discussed. Results showed that 1 can be a potential candidate for luminescence applications and can selectively adsorb methylene blue (MB) dye molecules. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Coordination polymers; 1,4-Phenylenediacetate; 1,2-Bis(4-pyridyl)ethane; Microwave-assisted method; Molecular simulation; Methylene blue